1990
DOI: 10.1039/p19900000541
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of benzotriazole with formaldehyde and aliphatic primary amines: selective formation of 1 : 1 : 1, of 2 : 2 : 1, and of 2 : 3 : 2 adducts and a study of their reactions with nucleophiles

Abstract: Benzotriazole ( BtH) reacts easily with aliphatic primary amines and formaldehyde in aqueous media to give one or more of three types of product: (i) (BtCH,),NR(5), (ii) (BtCH,NR),CH, (6), and/or (iii) BtCH,NHR (7). The product formed depends on the molar ratio of the substrates, and on the degree of steric hindrance in the amine, and is also influenced by the nature of the solvent. Primary aliphatic 1,2or 1,3-diamines yield cyclic aminals which are imidazolidine (8a) and hexahydropyrimidine (8b) derivatives. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…The NMR and MS data for 3b, 8f, 14d and 26-28 are presented as Supplementary material to this paper. Compound 14d was described either as a solid (m.p., 62-64 °C) 33 or as an oil, 34 but the reported NMR characteristics were quite similar. A new, simpler method of preparation of 14d (obtained as a solid) is proposed in the Supplementary material.…”
Section: Methodsmentioning
confidence: 78%
“…The NMR and MS data for 3b, 8f, 14d and 26-28 are presented as Supplementary material to this paper. Compound 14d was described either as a solid (m.p., 62-64 °C) 33 or as an oil, 34 but the reported NMR characteristics were quite similar. A new, simpler method of preparation of 14d (obtained as a solid) is proposed in the Supplementary material.…”
Section: Methodsmentioning
confidence: 78%
“…Hydrogenation gave the corresponding cis-and trans-2,5-disubstituted pyrrolidines 40 and 41 (Scheme 13) [52]. N,N-Bis(benzotriazol-1-ylmethyl)amines 42 [18,53] exist in equilibria with their ionic form 43 in solution. Such solutions were treated with samarium diiodide to generate radicals 44 which were rapidly reacted with various alkenes to provide more stable radicals 45.…”
Section: Pyrrolidinesmentioning
confidence: 99%
“…of benzotriazole provided 1,3-bis(benzotriazol-1-ylmethyl)imidazolidines 187. The reaction of crude 187 with KCN in acetonitrile gave dinitrile 188 and with Grignard reagents in THF afforded 1,3-dialkylimidazolidines 189 (Scheme 69) [53]. …”
Section: Scheme 66 Preparation Of Unsymmetrical 13-disubstituted Imimentioning
confidence: 99%
“…For the original monoclinic polymorph, see: Shoja & Saba (1993). For the synthesis of the title compound, see: Rivera et al (2004); Katritzky et al (1990). For the use of nitriles in synthesis, see: Prasad & Bhalla (2010).…”
Section: Related Literaturementioning
confidence: 99%
“…Single crystals of title compound were obtained by recrystallization from EtOH solution. An alternative synthetic method for the preparation of title compound involves the substitution of benzotriazolyl groups by cyano anion from the key benzotriazolyl intermediate 1,1′-(dihydropyrimidine-1,3(2H,4H)-diyldimethanediyl)-bis(1H-benzotriazole) (Katritzky et al, 1990) The molecular structure and atom-numbering scheme for (I) are shown in…”
Section: Data Collectionmentioning
confidence: 99%